Penerapan Sifat STAF Pada Pemasaran Madu Afifah Honeybee - Ivtin Kurniawati; Said Abadi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2023)
Introduction: This research discusses applying the characteristics of STAF (Siddiq, tabligh, Amanah, and fathanah) in Afifah Honeybee marketing to strengthen consumer decisions in buying Afifah Honeybee products. The nature of STAFF is viral among scholars but still needs to be widely applied in the business world; for this reason, this study intends to examine the application and impact of the nature of STAF in the business world. Research Methods: The research will produce qualitative descriptive data by using qualitative research methods and field research. Interview, observation, documentation techniques, data models, and drawing conclusions collected data. Results: The study results show that Afifah Honeybee's marketers have tried to apply the characteristics of STAF even though it could be more optimal. Conclusion: This application significantly positively impacts consumers' decisions to buy Afifah Honeybee's products.